Frequency of Survival of Endodontically Treated Teeth Restored With Filling or Crown - Nazir, Kiran; Ahmed, Alia; Awan, Fatima; Zaidi, Irha Hussain; Awan, Amina (Biological and Clinical Sciences Research Journal, 2025)
The long-term success of endodontically treated teeth significantly depends on the quality of the final restoration. Whether direct (fillings) or indirect (crowns), restorations are critical in protecting tooth structure and preventing reinfection. However, comparative survival outcomes of these restorations remain under-evaluated in clinical settings. Objective: To determine the survival frequency of endodontically treated teeth restored with either a direct filling or a crown. Methods: This cross-sectional descriptive study was conducted at the Department of Operative Dentistry, Islamic International Dental Hospital, Islamabad, from September 30, 2024, to March 29, 2025. One hundred six endodontically treated teeth from patients aged 13 to 60 were assessed. Dentists treated eligible cases with a minimum qualification of BDS. Clinical evaluation included assessing periodontal status, cracks or fractures, bleeding on probing, and attachment loss. Radiographic evaluation assessed the quality of root canal obturation and bone loss. Data were collected via case history interviews and analyzed using descriptive statistics in SPSS version 26. Results: The mean age of the participants was 37.79 ± 14.03 years, with a higher proportion of female patients. Out of 106 evaluated teeth, 97 (91.5%) remained clinically and radiographically successful following endodontic treatment and subsequent restoration with either a filling or a crown. Conclusion: This study demonstrates a high survival rate (91.5%) for endodontically treated teeth restored with either a filling or a crown, emphasizing the effectiveness of both restorative modalities in maintaining tooth integrity post-treatment.